Transformations of precedent sayings in the modern football discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
This article is devoted to analysis of transformation of precedent sayings in the modern football discourse. The phraseological transformation comprises the structural and semantic conversion of precedent sayings as aesthetical unites of human cognitive world.The thorough analysis demonstrates that phraseological substitution, which is change of composition of usual units and transfer it to a football discourse, is prevailing. The less quantity of transformations is represented phraseological expansion as a result of which usual unit passes to a football lexicon and concretizes it semantics. In modern football discourse phraseological contamination is confirmed, which combines: a) two usual phrasemes (sometimes transformed), b) usual and football phrasemes, c) two football phrasemes, sometimes distributed by various lexemes.The paper describes the transformations of proverbs related to specific football precedent situation. In those innovations we can see substitution of usual component which leads to a narrowing or refinement of their semantics. It has been distinguished such varieties of proverb transformation as: a) lexical substitution which consists in the replacing of the usual component of the simple sentenceproverbby the phrase; b) reduction of a negative particle which provides a transformation of affirmative modality; c) lexical substitution consisting in the replacing ofusual component of complex sentenceproverbby the football proper name or term; d) double lexical substitution is the replacement of the usual components of proverb in both parts of the complex sentence; e) syntactic substitution which involves the complete replacing of one part of a complex sentence; f) syntactic expansion, consisting in the expansion of proverb by a phrase, part of a complex sentence or a separate complex sentence.The usual component of phraseme can be replaced by a football anthroponym, a football appeal lexeme, and a quantitative-noun phrase. The transformations of precedent sayings give the text expressiveness; reveal its essence in the consciousness of the football lingua-cultural community, but for their full understanding, knowledge of the national verbal code and specific precedent situations is required.
Keywords: precedent saying; transformation; phraseology; phraseme; proverb; innovation; modern football discourse